Model comparison of Yamato and Allan Hills polymict eucrites - Delaney, Jeremy S.; Takeda, Hiroshi; Prinz, Martin (1983)
P(論文) Comparison of modal analyses of seven Yamato and six Allan Hills polymict eucrite specimens reveals differences of plagioclase and pyroxene content between the two groups. The Yamato suite has more "pigeonitic' pyroxene and less plagioclase and low calcium pyroxene than the Allan Hills suite. Variations within each suite are small and three sections of Allan Hills A78040 are more variable than the Allan Hills suite considered as a group. Modal data provides a basis for pairing polymict eucrite specimens when used together with mineralogical and petrographic criteria. The Yamato suite is tentatively considered to sample three meteorites although further work may reduce this number to two. The Allan Hills suite presently samples two meteorites. Modal data also provides constraints on the petrography of the rock types sampled by these polymict eucrites, and in addition to confirming the presence of several rock types previously identified using pyroxene crystallography, hints at the presence of an augite-rich component. departmental bulletin paper